2000
DOI: 10.1088/0268-1242/15/8/308
|View full text |Cite
|
Sign up to set email alerts
|

The role of boundary conditions in shot noise in elastic diffusive conductors

Abstract: The role played by boundary conditions at a kinetic level in determining the noise properties of mesoscopic diffusive conductors is evaluated by decomposing the current fluctuations, into fluctuations of boundaries, self-consistent electric potential and the intrinsic Langevin source. We show that the self-consistent contribution is essentially controlled by the range of energies determined by the distribution function at the contacts together with the differential conductivity in energy space. The intrinsic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…If this is not the case, the eq. (51) should be modified correspondingly 39 . The "random source" δj ext is generated by short-range scattering events of conducting electrons on the impurities.…”
Section: Current Noise In Disordered Junctionsmentioning
confidence: 99%
“…If this is not the case, the eq. (51) should be modified correspondingly 39 . The "random source" δj ext is generated by short-range scattering events of conducting electrons on the impurities.…”
Section: Current Noise In Disordered Junctionsmentioning
confidence: 99%
“…In computer simulations one can consider any value of the momentum-space dimensionality d. Thus, even if the physically relevant case is dϭ3, we will analyze also the case dϭ2, since for this value of d there exist analytical predictions based on the same assumptions on what concerns the coupling of the kinetic equation with the Poisson equation. [7][8][9][10][11][12] As indicated in Ref. 8, this case corresponds to a hypothetical ''flatland'' whose physical realization would be a layered material with each layer containing a two-dimensional electron gas.…”
Section: Physical Modelmentioning
confidence: 99%
“…12 concerning the shot-noise properties of nondegenerate elastic diffusive conductors. In that work, by means of a formal treatment of the Boltzmann-Langevin-Poisson set of equations it was shown that the Fano factor for this class of systems can be exactly decomposed into the sum of three contributions as ␥ϭ␥ in ϩ␥ ϩ␥ in, .…”
Section: Theoretical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, one can neglect long range Coulomb interaction effects on the fluctuations, 27 thus simplifying considerably the calculations.…”
Section: Strongly Degenerate Systemsmentioning
confidence: 99%